Cloudonomics : the business value of cloud computing - Weinman, Joe, 1958- (Hoboken, N.J. : Wiley, 2012)
"The ultimate guide to assessing and exploiting the customer value and revenue potential of the CloudA new business model is sweeping the world--the Cloud. And, as with any new technology, there is a great deal of fear, uncertainty, and doubt surrounding cloud computing. Cloudonomics radically upends the conventional wisdom, clearly explains the underlying principles and illustrates through understandable examples how Cloud computing can create compelling value--whether you are a customer, a provider, a strategist, or an investor. Cloudonomics covers everything you need to consider for the delivery of business solutions, opportunities, and customer satisfaction through the Cloud, so you can understand it--and put it to work for your business. Cloudonomics also delivers insight into when to avoid the cloud, and why. Quantifies how customers, users, and cloud providers can collaborate to create win-wins Reveals how to use the Laws of Cloudonomics to define strategy and guide implementation Explains the probable evolution of cloud businesses and ecosystemsDemolishes the conventional wisdom on cloud usage, IT spend, community clouds, and the enterprise-provider cloud balance Whether you're ready for it or not, Cloud computing is here to stay. Cloudonomics shows how the business model of the Cloud offers insights to executives, practitioners, and strategists in virtually any industry--not just technology executives but also those in the marketing, operations, economics, venture capital, and financial fields"--
Includes bibliographical references and index.
Keywords: Cloud computing -- Economic aspects; Information technology -- Management; COMPUTERS / General